Ответы и объяснения

2013-02-14T10:52:00+04:00

(3x-1)^2 = 3(1-2x)                                   (x+3)^2 = 3(x+1)^2

9х^2 - 6x+1-3+6x=0                                x^2+6x+9=3x^2 +6x+3

9x^2-2=0                                                   2x^2=6

x^2= 2/9                                                     x^2=3

x= sqrt2 / 3 , -sqrt2/3                               x=sqrt3  ( корень из 3 )

2013-02-14T10:57:11+04:00

(3х-1)²=3(1-2х)

9х²-6х+1=3-6х

9х²-6х+6х+1-3=0

9х²-2=0

9х²=2

х²=2/9

х=\sqrt{2} / 3

ответ \sqrt{2} / 3


х²+6х+9=3(х²+2х+1)

х²+6х+9=3х²+6х+3

3х²-х²+6х-6х+3-9=0

2х²-6=0

х²-3=0

х²=3

х=√3

ответ √3